Proposals for Annual Plan 1973-74 Andaman and Nicobar Administration - Planning Commission (Planning Commission, 1973)
While undertaking the mid-term appraisal of the 4th Plan it was felt that some sectoral reallocation of funds was necessary. This reallocation was done within the original outlay of Rs.1400.00 lakhs for the 4th Plan as a whole. The review undertaken in the beginning of 1972-73 brought to light additional factors that could not have been foreseen earlier Taking these into consideration and also the fact that the capacity of the economy to incur developmental expenditure in its different sectoral aspects has increased over the years, requirements under various sectors were worked out again.
Andaman and Nicobar Administration